Glass ceramic article with increased crush resistance and method of making same

Through specific heating treatment methods and heat treatment parameter control, glass ceramic products with high breakage toughness and low haze are formed, which solves the problem of insufficient anti-breakability of glass ceramic products in the prior art, and is suitable for covering substrates and shells of mobile electronic devices.

CN119797767APending Publication Date: 2025-04-11CORNING INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510015518.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2018-09-26
Filing Date
2019-07-09
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Existing glass ceramic products have shortcomings in their resistance to crushing, especially in cover substrates and housing applications of mobile electronic devices, and it is necessary to improve their mechanical properties such as crack permeability and drop resistance while maintaining appropriate optical properties.

Method used

The glass is converted into glass ceramics through a specific heating treatment method to form a structure with one or more crystal phases and residual glass phases, and a compressive stress layer is formed on the surface to improve its crushing toughness and store tensile energy. At the same time, its optical characteristics and haze are adjusted by controlling the nucleation temperature, crystallization temperature and heat treatment time.

Benefits of technology

It realizes high breaking toughness, storage tensile energy and low haze of glass ceramic products, improves its crack permeability and drop performance, while maintaining appropriate optical characteristics, suitable for cover substrates and shells of mobile electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797767A_ABST
    Figure CN119797767A_ABST
Patent Text Reader

Abstract

A glass ceramic article having: one or more crystalline phases; remaining a glass phase; a compressive stress layer extending from the first surface to a depth of compression (DOC); a maximum center tension greater than 70 MPa; a storage tensile energy greater than 22 J / m2; a fragmentation toughness greater than 1.0 MPa square root of m; and a haze of less than 0.2.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of a patent application with an application date of July 9, 2019, application number 201980005720.8, and name “Glass-ceramic products with increased breakage resistance and methods for manufacturing the same”.

[0002] CROSS-REFERENCE TO RELATED APPLICATIONS

[0003] This application claims priority under 35 U.S.C. §119 to U.S. Provisional Application Serial No. 62 / 698,532, filed on July 16, 2018, and U.S. Provisional Application Serial No. 62 / 736,682, filed on September 26, 2018, which are hereby relied upon and are incorporated herein by reference in their entirety. Technical Field

[0004] The present disclosure relates to glass-ceramic articles having increased crush resistance, and more particularly, to ion-exchanged glass-ceramic articles having high crush toughness and stored tensile energy and low haze, and ceramizing schemes for their manufacture. Background Art

[0005] Glass ceramic articles can be used as cover substrates and housings for mobile electronic devices. In some cases, glass ceramic articles can have better mechanical properties than glass in terms of mechanical properties such as crack penetration resistance and drop performance. Crack penetration resistance and drop performance are important mechanical properties for cover substrates and housings for mobile electronic devices, and there is a need to increase these mechanical properties in glass ceramic articles.

[0006] When glass-ceramic articles are used as covering substrates (where transparency is important), it is desirable that the glass-ceramic have suitable optical properties. The optical properties can be achieved by heat treatments that convert the glass into a glass-ceramic. Improved heat treatments are needed to achieve the desired optical properties in glass-ceramic articles. Summary of the invention

[0007] In the first aspect, the glass-ceramic article comprises: a first surface; a second surface opposite the first surface; one or more crystalline phases; a residual glass phase; a compressive stress layer extending from the first surface to a depth of compression (DOC); a maximum central tension greater than 70 MPa; and a tensile strength greater than 22 J / m 2 greater than 1.0 MPa√m of the crushing toughness, wherein the crushing toughness is measured for the following glass-ceramics, the composition and phase assembly of the glass-ceramics are equivalent to the composition and phase assembly at the center of the glass-ceramic article; and a haze of less than 0.2.

[0008] In a second aspect, the glass-ceramic article comprises: a first surface; a second surface opposite the first surface; one or more crystalline phases; a residual glass phase; a compressive stress layer extending from the first surface to a depth of compression (DOC); a maximum central tension greater than 70 MPa; and a tensile strength greater than 22 J / m 2 greater than 95 GPa Young's modulus, wherein the Young's modulus is measured for the following glass-ceramics, the composition and phase assembly of the glass-ceramics are equivalent to the composition and phase assembly at the center of the glass-ceramic article; and a haze of less than 0.2.

[0009] In a third aspect, the glass-ceramic article comprises: a first surface; a second surface opposite the first surface; one or more crystalline phases; a residual glass phase; a compressive stress layer extending from the first surface to a depth of compression (DOC); a maximum central tension greater than 70 MPa; and a tensile strength greater than 22 J / m 2 storage tensile energy; ZrO2 is 1.7 mol% to 4.5 mol%; and the ratio of LiO2 (mol%) / R2O (mol%) is greater than 0.85, wherein R2O is the sum of alkali metal oxides.

[0010] In a fourth aspect, a method of forming a glass ceramic article, the method comprising: heating a glass composition to a nucleation temperature to produce a nucleated crystallizable glass composition; heating the nucleated crystallizable glass composition to a crystallization temperature; and maintaining the crystallization temperature for a predetermined period of time to produce a glass ceramic article, wherein the glass ceramic article comprises a crushing toughness greater than 1.0 MPa√m; and a haze less than 0.2.

[0011] In a fifth aspect, a method of forming a glass-ceramic article comprises: heating a glass composition to a nucleation temperature (T N ); maintaining the nucleation temperature for a first predetermined period of time (t N ) to produce a nucleated crystallizable glass composition; heating the nucleated crystallizable glass composition to a crystallization temperature (T C ); and maintaining the crystallization temperature for a second predetermined period of time (t C ) to produce glass ceramic products, where (103–0.260T N +0.000203(T N ) 2 –7.96t N +0.1532(t N ) 2 –0.019T C –0.000008(T C ) 2 –10.03t C +0.00597T N *tN +0.00463t N *T C +0.01342T C *t C )<0.2.

[0012] In a sixth aspect, a method for controlling the haze of a glass-ceramic article comprises: adjusting a nucleation temperature (T N ), the first predetermined time period (t N ), crystallization temperature (T C ) and a second predetermined time period (t C ) is selected so that (103–0.260T N +0.000203(T N ) 2 –7.96t N +0.1532(t N ) 2 –0.019T C –0.000008(T C ) 2 –10.03t C +0.00597T N *t N +0.00463t N *T C +0.01342T C *t C )<0.2.

[0013] Other features and advantages of the present invention are set forth in the following detailed description, some of which will be readily apparent to those skilled in the art from the description or recognized by practicing the various embodiments described herein, including the following detailed description, claims, and accompanying drawings.

[0014] It is to be understood that the above general description and the following detailed description are merely exemplary and are intended to provide an overall review or framework for understanding the nature and character of the claims. The accompanying drawings provide a further understanding and are incorporated into and constitute a part of this specification. The drawings illustrate one or more embodiments and together with the description serve to explain the principles and operation of the various embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 is an exemplary cross-sectional view of a strengthened glass-ceramic article;

[0016] Figure 2 is an example diagram of a cooling cycle;

[0017] Figure 3is another example diagram of a cooling cycle;

[0018] Figure 4A is a plan view of an exemplary electronic device incorporating any of the glass-ceramic articles disclosed herein;

[0019] Figure 4B yes Figure 4A A perspective view of an exemplary electronic device;

[0020] Figure 5 is a stress distribution diagram of Example 1;

[0021] Figure 6 is a central tension graph of Example 2 with increasing duration of ion exchange;

[0022] Figure 7 is a phase assembly of the glass-ceramic of Example 3; and

[0023] Figure 8 This is a transmittance graph of the glass ceramic of Example 3. DETAILED DESCRIPTION

[0024] Definition and measurement techniques

[0025] As used herein, the term "glass-ceramic" is a solid prepared by controlled crystallization of a precursor glass and having one or more crystalline phases and a residual glass phase.

[0026] As used herein, "depth of compression" or "DOC" refers to the depth of the compressive stress (CS) layer and is the depth at which the stress in the glass-ceramic article changes from compressive stress to tensile stress and the stress value is zero. According to common practice in the art, compressive stress is expressed as negative stress (<0) and tensile stress is expressed as positive stress (>0). However, throughout this specification, unless otherwise stated, CS is expressed as a positive value or an absolute value, that is, CS=|CS| as stated herein.

[0027] The DOC and CT values ​​were measured using a scattered light polarimeter (SCALP) model SCALP-04 purchased from Glasstress Ltd., located in Tallinn, Estonia.

[0028] The surface CS measurement method depends on whether a glassy area or layer is formed at the surface of the glass-ceramic article during the ion exchange process. If there is no glassy layer or area, the surface CS is measured by a surface stress meter (FSM) using a commercial instrument (e.g., FSM-6000) manufactured by Orihara Industrial Co., Ltd. (Japan). Surface stress measurement relies on the accurate measurement of the stress optical coefficient (SOC), which is related to the birefringence of the glass ceramic. SOC is then measured according to Scheme C (Glass Disc Method) described in ASTM Standard C770-16, entitled "Standard Test Method for Measurement of Glass Stress-Optical Coefficient", the entire text of which is incorporated herein by reference. If a glassy region or layer is formed, the surface CS (as well as the CS in the glassy layer or region) is measured as follows: in the prism coupling measurement, the birefringence of the first transmission (coupling) resonance of the glassy region is measured, and the layer depth of the glassy region is measured by the spacing between the first and second transmission resonances or the width of the first transmission resonance.

[0029] The CS in the remaining CS region is measured by a refractive near field (RNF) method as described in U.S. Pat. No. 8,854,623, entitled "Systems and methods for measuring a profile characteristic of a glass sample," which is incorporated herein by reference in its entirety. The RNF measurement is force balanced and calibrated by the maximum CT value provided by the SCALP measurement. Specifically, the RNF method includes placing the glass article near a reference block, generating a polarization-switched beam (which switches between orthogonal polarizations at a rate of 1 Hz to 50 Hz), measuring the amount of power in the polarization-switched beam, and generating a polarization-switched reference signal, wherein the measured amount of power in each orthogonal polarization is within 50% of each other. The method also includes passing the polarization-switched beam through the glass sample and the reference block into the glass sample at different depths, and then using a delay optical system to delay the passing polarization-switched beam to reach a signal light detector, which generates a polarization-switched detector signal. The method also includes: dividing the detector signal by the reference signal to form a normalized detector signal, and determining the profile characteristic of the glass sample from the normalized detector signal.

[0030] The stress distribution can be measured by a combination of RNF for the inner CS, SCALP for the CT region, and a method for measuring the surface CS.

[0031] The stored tensile energy (in J / m) is calculated using the following equation (1): 2 ):

[0032] Stored tensile energy (J / m 2 )=[(1-ν) / E]∫(σ 2 )(dt)(1)

[0033] Where ν is Poisson's ratio, E is Young's modulus, σ is stress, t is thickness, and the integral is calculated over the thickness of the stretched region only.

[0034] The crystalline phase assembly (before ion exchange) and the weight percentages of crystalline phases and residual glassy phases were determined using Rietveld analysis based on X-ray diffraction (XRD).

[0035] The following procedure (referred to herein as the "fragment test") is used to determine the number of fragments into which a glass-ceramic article breaks after being crushed. An ion-exchanged glass-ceramic article having dimensions of 50 mm by 50 mm by 0.8 mm is placed on a steel surface, such as an MVN precision vertical table available from Newport Corporation. A 40 g tungsten carbide tipped stylus (available from Fisher Scientific Industries, trade name ) is placed on the surface of the glass-ceramic article. and manufacturer identification number #13-378, with a 60 degree conical tip) is connected to a fixture on a gear drive mechanism that moves the stylus up and down. The tip of the stylus is placed in contact with the glass ceramic article, and the gear mechanism is then adjusted in increments until the glass ceramic article breaks. The number of fragments is then counted.

[0036] The crushing toughness value (K) was measured by the chevron notched short bar (CNSB) method. 1C), which is disclosed in Reddy, KPR et al., "Fracture Toughness Measurement of Glass and Ceramic Materials Using Chevron-Notched Specimens", J. Am. Ceram. Soc., 71[6], C-310-C-313 (1988), except that Bubsey, RT et al., "Closed-Form Expressions for Crack-Mouth Displacement and Stress Intensity Factors for Chevron-Notched Short Bar and Short Rod Specimens Based on Experimental Compliance Measurements", NASA Technical Memorandum 83796, pp. 1-30 (October 1992) Equation 5 is used to calculate Y* m . Measured on glass ceramics without ion exchange (K 1C ). For ion-exchanged glass-ceramic products, K can be measured on such non-ion-exchanged glass-ceramic products. 1C , the non-ion exchanged glass-ceramic article has an equivalent composition and crystal phase set as the center (half thickness) of the ion exchanged glass-ceramic article. The composition at the center of the ion exchanged glass-ceramic article can be determined by a microprobe by performing a line scan from surface to surface and determining the composition at the center, and then determining the crystal phase set at the center by x-ray diffraction.

[0037] The Young's modulus value stated in the present disclosure refers to the value measured by the resonance ultrasonic spectroscopy technology of the general type described in ASTM E2001-13. Young's modulus is measured on the glass-ceramic product without ion exchange. For the glass-ceramic product through ion exchange, Young's modulus can be measured on such glass-ceramic product without ion exchange, and the glass-ceramic product without ion exchange has the composition and crystalline phase set equivalent to the center (half thickness) of the glass-ceramic product through ion exchange. The composition at the center of the glass-ceramic product through ion exchange can be determined in the following manner by microprobe: line scan from surface to surface and determine the composition at the center, then determine the crystalline phase set at the center by x-ray diffraction.

[0038] The haze of the glass-ceramic article is measured by using a haze meter (eg, BYK Gardner Haze-Gardi).

[0039] As used herein, transmittance refers to total transmittance and is measured using a Perkin Elmer Lambda 950 UV / VIS / NIR spectrophotometer with a 150 mm integrating sphere. The sample is mounted to the entrance end of the sphere to enable collection of wide angle scattered light. Total transmittance data is collected using a reference Spectralon reflector disk on the exit end of the sphere. The percentage of total transmittance (%T) is calculated relative to an open beam baseline measurement.

[0040] Overview of properties of glass ceramic products

[0041] Reference will now be made in detail to the preferred embodiments of the present invention, examples of which are illustrated in the accompanying drawings. Whenever possible, the same reference numerals are used throughout the drawings to refer to the same or like parts.

[0042] The property of glass-ceramic products can be adjusted so as to be used as a covering substrate and / or housing for mobile electronic devices. For example, without being limited to theory, glass-ceramic products with high crushing toughness and / or Young's modulus can provide crack resistance and drop performance. When such glass-ceramic products are chemically strengthened by, for example, ion exchange, crack resistance and drop performance can be further strengthened. And high crushing toughness and / or Young's modulus can also increase the tensile energy and maximum center tension force stored, which can be given to glass-ceramic products by chemical tempering, while maintaining the fragmentation of glass-ceramic desired after crushing. For example, the optical properties (for example, transparency and haze) of glass-ceramic products can be adjusted in the following manner: by adjusting the heating / ceramicization scheme for converting glass products into glass-ceramic products, and by chemical strengthening (for example, by ion exchange) to design or control the properties of glass-ceramic products.

[0043] Figure 1 An exemplary cross-sectional side view of a strengthened glass-ceramic article 100 is shown having a first surface 102 and an opposing second surface 104 separated by a thickness (t). In some embodiments, the strengthened glass-ceramic article 100 is ion exchanged and has a compressive stress (CS) layer 106 (or first region) extending from the first surface 102 to a depth of compression (DOC). In some embodiments, as Figure 1As shown, the glass ceramic article 100 also has a compressive stress (CS) layer 108 extending from the second surface 104 to a compression depth DOC'. There is also a central tension region 110 between DOC and DOC' that is under tensile stress. In some embodiments, DOC and DOC' can be in the following ranges: greater than 0*t to 0.3*t, 0*t to 0.25*t, 0*t to 0.2*t, 0*t to 0.15*t, 0*t to 0.1*t. 0*t to 0.05*t. 0.05*t to 0.3*t, 0.05*t to 0.25*t, 0.05*t to 0.2*t, 0.05*t to 0.15*t, 0.05*t to 0.1*t, 0.1*t to 0.3*t, 0.1*t to 0.25*t, 0.1*t to 0.2*t, 0.1*t to 0.15*t, and all ranges and sub-ranges therebetween, where t is the thickness of the glass-ceramic article 100. For example, the depth of the compressive stress layer (DOC, DOC') may be greater than 0.05*t, 0.06*t, 0.07*t, 0.08*t, 0.09*t, 0.1*t, 0.11*t, 0.12*t, 0.13*t, 0.14*t, 0.15*t, 0.16*t, 0.17*t, 0.18*t, 0.19*t, 0.2*t, 0.21*t, 0.22*t, 0.23*t, 0.24*t, 0.25*t, 0.26*t, 0.27*t, 0.28*t, 0.29*t or 0.3*t. In other embodiments, the depth of the compressive stress layer (DOC, DOC') is: 0.05mm to .6mm, 0.05mm to 0.5mm, 0.05mm to 0.4mm, 0.05mm to 0.3mm, 0.05mm to 0.2mm, 0.05mm to 0.1mm, 0.1mm to 0.6mm, 0.1mm to 0.5mm, 0.1mm to 0.4mm, 0.1mm to 0.3mm, 0.2mm to 0.6mm, 0.2mm to 0.5mm, 0.2mm to 0.4mm, and all ranges and sub-ranges therebetween. In some embodiments, the depth of the compressive stress layer is greater than or equal to 0.05 mm, 0.06 mm, 0.07 mm, 0.08 mm, 0.09 mm, 0.1 mm, 0.15 mm, 0.2 mm, 0.25 mm, 0.3 mm, 0.35 mm, 0.4 mm, 0.45 mm, 0.5 mm, 0.55 mm, or 0.6 mm. In some embodiments, DOC may be equal to DOC'. In some embodiments, DOC may be different from DOC'.

[0044] In some embodiments, the maximum central tension (CT) is greater than 70 MPa to 180 MPa. In some embodiments, the maximum CT is greater than or equal to 70 MPa, 80 MPa, 90 MPa, 100 MPa, 110 MPa, 120 MPa, 130 MPa, 140 MPa, 150 MPa, 160 MPa or 170 MPa. In some embodiments, the maximum CT may be in the range of greater than 70 MPa to 180 MPa, greater than 70 MPa to 170 MPa, greater than 70 MPa to 160 MPa, greater than 70 MPa to 150 MPa, greater than 70 MPa to 140 MPa, greater than 80 MPa to 180 MPa, greater than 80 MPa to 170 MPa, greater than 80 MPa to 160 MPa, greater than 80 MPa to 150 MPa, greater than 80 MPa to 140 MPa, greater than 90 MPa to 180 MPa, greater than 90 MPa to 170 MPa, greater than 90 MPa to 160 MPa, greater than 90 MPa to 150 MPa, greater than 90 MPa to 140 MPa, 100 MPa to 180 MPa. MPa, 100 MPa to 170 MPa, 100 MPa to 160 MPa, 100 MPa to 150 MPa, 100 MPa to 140 MPa, 110 MPa to 180 MPa, 110 MPa to 170 MPa, 110 MPa to 160 MPa, 110 MPa to 150 MPa, 110 MPa to 140 MPa, 120 MPa to 180 MPa, 120 MPa to 170 MPa, 120 MPa to 160 MPa, 120 MPa to 150 MPa, 120 MPa to 140 MPa, 130 MPa to 180 MPa, 130 MPa to 170 MPa, 130 MPa to 1500 MPa, or any range or subrange therebetween.

[0045] In some embodiments, the storage tensile energy of the glass-ceramic article is in the following range: greater than 22 J / m 2 Up to 100J / m 2 , greater than 22J / m 2 Up to 90J / m 2 、 More than 22J / m 2 Up to 80J / m 2 、 More than 22J / m 2 Up to 70J / m 2 、 More than 22J / m 2 Up to 65J / m 2 、 More than 22J / m 2 Up to 60J / m 2 More than 22J / m 2Up to 55J / m 2 、 More than 22J / m 2 Up to 50J / m 2 , greater than 22J / m 2 Up to 45J / m 2 , greater than 22J / m 2 Up to 40J / m 2 , greater than 22J / m 2 Up to 35J / m 2 , greater than 22J / m 2 Up to 30J / m 2 , 25J / m 2 Up to 100J / m 2 , 25J / m 2 Up to 90J / m 2 , 25J / m 2 Up to 80J / m 2 , 25J / m 2 Up to 70J / m 2 , 25J / m 2 Up to 65J / m 2 , 25J / m 2 Up to 60J / m 2 , 25J / m 2 Up to 55J / m 2 , 25J / m 2 Up to 50J / m 2 , 25J / m 2 Up to 45J / m 2 , 25J / m 2 Up to 40J / m 2 , 25J / m 2 Up to 35J / m 2 , 25J / m 2 Up to 30J / m 2 、30J / m 2 Up to 100J / m 2 、30J / m 2 Up to 90J / m 2 、30J / m 2 Up to 80J / m 2 、30J / m 2 Up to 70J / m 2 、30J / m 2 Up to 65J / m 2 、30J / m 2 Up to 60J / m 2 、30J / m 2 Up to 55J / m 2 、30J / m 2 Up to 50J / m 2 、30J / m2 Up to 45J / m 2 、30J / m 2 Up to 40J / m 2 、30J / m 2 Up to 35J / m 2 、35J / m 2 Up to 60J / m 2 、35J / m 2 Up to 100J / m 2 、35J / m 2 Up to 90J / m 2 、35J / m 2 Up to 80J / m 2 、35J / m 2 Up to 70J / m 2 、35J / m 2 Up to 65J / m 2 、35J / m 2 Up to 60J / m 2 、35J / m 2 Up to 55J / m 2 、35J / m 2 Up to 50J / m 2 、35J / m 2 Up to 45J / m 2 、35J / m 2 Up to 40J / m 2 , 40J / m 2 Up to 100J / m 2 , 40J / m 2 Up to 90J / m 2 , 40J / m 2 Up to 80J / m 2 , 40J / m 2 Up to 70J / m 2 , 40J / m 2 Up to 65J / m 2 , 40J / m 2 Up to 60J / m 2 , 40J / m 2 Up to 55J / m 2 , 40J / m 2 Up to 50J / m 2 , 40J / m 2 Up to 45J / m 2 , 45J / m 2 Up to 100J / m 2 , 45J / m 2 Up to 90J / m 2 , 45J / m 2 Up to 80J / m 2 , 45J / m 2Up to 70J / m 2 , 45J / m 2 Up to 65J / m 2 , 45J / m 2 Up to 60J / m 2 , 45J / m 2 Up to 55J / m 2 , 45J / m 2 Up to 50J / m 2 、65J / m 2 Up to 100J / m 2 、65J / m 2 Up to 90J / m 2 、65J / m 2 Up to 80J / m 2 、65J / m 2 Up to 70J / m 2 , and all ranges and subranges therebetween. In some embodiments, the stored tensile energy may be greater than or equal to 22 J / m 2 、23J / m 2 、24J / m 2 , 25J / m 2 、30J / m 2 、35J / m 2 , 40J / m 2 , 45J / m 2 , 50J / m 2 、55J / m 2 、60J / m 2 、65J / m 2 、70J / m 2 , 75J / m 2 、80J / m 2 、85J / m 2 , 90J / m 2 or 95 J / m 2 In some embodiments, such as when a fragmentation test of less than 5 fragments is desired, the storage tensile energy of the glass-ceramic article is greater than 22 J / m 2 Up to 65J / m 2 .

[0046] In some embodiments, the thickness t of the glass-ceramic article is in the range of 0.2 mm to 4 mm, 0.2 mm to 3 mm, 0.2 mm to 2 mm, 0.2 mm to 1.5 mm, 0.2 mm to 1 mm, 0.2 mm to 0.9 mm, 0.2 mm to 0.8 mm, 0.2 mm to 0.7 mm, 0.2 mm to 0.6 mm, 0.2 mm to 0.5 mm, 0.3 mm to 4 mm, 0.3 mm to 3 mm, 0.3 mm to 2 mm, 0.3 mm to 1.5 mm, 0.3 mm to 1 mm, 0.3 mm to 0.9 mm, 0.3 mm to 0.8 mm, 0.3 mm to 0.7 mm, 0.3 mm to 0.6 mm, 0.3 mm to 0.5 mm, 0.4 mm to 4 mm, 0. In some embodiments, the glass-ceramic article can be substantially planar and flat. In other embodiments, the glass-ceramic article may be shaped, for example, may have a 2.5D or 3D shape. In some embodiments, the glass-ceramic article may have a uniform thickness, while in other embodiments, the glass-ceramic article may not have a uniform thickness.

[0047] In some embodiments, the crushing toughness of the glass-ceramic article is in the range of 1.0 MPa√m to 2.0 MPa√m, 1.1 MPa√m to 2.0 MPa√m, 1.2 MPa√m to 2.0 MPa√m, 1.3 MPa√m to 2.0 MPa√m, 1.4 MPa√m to 2.0 MPa√m, 1.5 MPa√m to 2.0 MPa√m, 1.0 MPa√m to 1.9 MPa√m, 1.1 MPa√m to 1.9 MPa√m, 1.2 MPa√m to 1.9 MPa√m, 1.3 MPa√m to 1.9 MPa√m, 1.4 MPa√m to 1.9 MPa√m, 1.5 MPa√m to 1.9 MPa√m, 1.0 MPa√m to 1.8 MPa√m, 1.1 MPa√m to 1.8 MPa√m, 1.2 MPa√m to 1.8 MPa√m, 1.3 MPa√m to 1.8 MPa√m, 1.4 MPa√m to 1.8 MPa√m, 1.5 MPa√m to 1.8 MPa√m, and all ranges and subranges therebetween. In some embodiments, the crush toughness of the glass-ceramic article is greater than or equal to 1.0 MPa√m, 1.1 MPa√m, 1.2 MPa√m, 1.3 MPa√m, 1.4 MPa√m, 1.5 MPa√m, 1.6 MPa√m, 1.7 MPa√m, 1.8 MPa√m or 1.9 MPa√m. Without being limited by theory, the glass-ceramic article having a crush toughness in this range achieves an increase in stored tensile energy that results in less than 5 fragments under a fragment test.

[0048] In some embodiments, the Young's modulus of glass ceramic article is as follows: 95GPa to 110GPa, 95GPa to 105GPa, 95GPa to 100GPa, 100GPa to 110GPa, 100GPa to 105GPa, 105GPa to 110GPa, and all ranges and sub-ranges therebetween. In some embodiments, the Young's modulus of glass ceramic article is greater than or equal to 95GPa, 96GPa, 97GPa, 98GPa, 99GPa, 100GPa, 101GPa, 102GPa, 103GPa, 104GPa, 105GPa, 106GPa, 107GPa, 108GPa or 109GPa. Without being limited to theory, the glass ceramic article with the crushing toughness of this scope realizes an increase in the storage tensile energy that causes less than 5 fragments under the fragment test.

[0049] In some embodiments, the glass-ceramic article breaks into fewer than 5 fragments, fewer than 4 fragments, or fewer than 3 fragments after applying the fragment test described above (based on a 50 mm by 50 mm by 0.8 mm sample).

[0050] composition

[0051] Precursor glass and glass ceramic as described herein can be generally described as containing lithium aluminosilicate glass or glass ceramic, and comprise SiO , Al O and Li O.Except SiO , Al O and Li O, the glass and glass ceramic practiced herein can also contain alkaline salts (such as Na O, K O, Rb O or Cs O) and P O and ZrO , and many other components described below.In some embodiments, in the molar percentage of oxide, precursor glass (before ceramization) and / or glass ceramic (after ceramization) can have following composition:

[0052] SiO2: 60-72%;

[0053] Al2O3: 0-6%;

[0054] Li2O: 20-32%;

[0055] B2O3: 0-2%;

[0056] Na2O: 0-2%;

[0057] K2O: 0-2%;

[0058] P2O5: 0.7-2.2%; and

[0059] ZrO2: 1.7-4.5%.

[0060] In some embodiments, the precursor glass and / or glass ceramic may have the following optional additional components, measured in mole percent of oxides:

[0061] SnO2: 0.05-0.5%;

[0062] Fe2O3: 0-0.5%;

[0063] MgO: 0-1%;

[0064] ZnO: 0-1%;

[0065] BaO: 0-1%;

[0066] SrO: 0-1%;

[0067] La2O3: 0-1%;

[0068] GeO2: 0-1%;

[0069] Ta2O5: 0-1%;

[0070] Table 1 below lists exemplary precursor glass and glass-ceramic compositions in terms of mole % of metal oxides.

[0071] Table 1

[0072]

[0073]

[0074] Table 1 continued

[0075] composition 8 9 10 11 12 13 <![CDATA[SiO2 (mol%)]]> 70 71.2 70.9 70.3 70.2 70.30 <![CDATA[Al2O3 (mol%)]]> 4.3 4.6 4.9 3.8 4.3 4.23 <![CDATA[B2O3 (mol%)]]> 0 0 0 0 0 0 <![CDATA[Li2O (mol%)]]> 21.9 21.2 21.3 22 21.9 21.36 <![CDATA[Na2O (mol%)]]> 1 0 0 0 0 1.51 <![CDATA[K2O (mol%)]]> 0 0 0 0 0 0 <![CDATA[P2O5 (mol%)]]> 0.9 0.9 0.9 0.9 0.9 0.87 <![CDATA[ZrO2 (mol%)]]> 2 2 2 3 2.7 1.66 <![CDATA[SnO2 (mol%)]]> 0 0 0 0 0 0 <![CDATA[Fe2O3 (mol%)]]> 0 0 0 0 0 0 <![CDATA[Li2O / R2O]]> 0.96 1.00 1.00 1.00 1.00 0.93

[0076] SiO , relates to glass-forming oxides, which can play a role in stabilizing the network structure of glass and glass-ceramic. In some embodiments, glass or glass-ceramic composition comprises about 60 to about 72 mol % SiO . In some embodiments, glass or glass-ceramic composition can comprise about 60 to about 72 mol %, about 60 to about 70 mol %, about 60 to about 67 mol %, about 60 to about 65 mol %, 65 to about 72 mol %, about 65 to about 70 mol %, about 65 to about 67 mol % SiO , and all ranges and sub-ranges therebetween. In some embodiments, glass or glass-ceramic composition comprises about 60,61,62,63,64,65,66,67,68,69,70,71 or 72 mol % SiO .

[0077] For viscosity and mechanical properties, viscosity and mechanical properties are affected by glass composition. In glass and glass ceramics, SiO2 plays the main glass-forming oxide for precursor glass and can play the function of stabilizing the network structure of glass and glass ceramics. The amount of SiO2 can be limited to control the melting temperature (200 poise temperature) because the melting temperature of pure SiO2 or high SiO2 glass is undesirably high.

[0078] Al2O3 can also provide network stabilization, and can also provide improved mechanical properties and chemical durability. However, if the amount of Al2O3 is too high, the proportion of lithium silicate crystals may decrease, and may decrease to the extent that an interlocking structure cannot be formed. The amount of Al2O3 can be adjusted to control the viscosity. In addition, if the amount of Al2O3 is too high, the viscosity of the melt is generally increased. In some embodiments, the glass or glass ceramic composition may contain about 0 to about 6 mol % Al2O3, and all ranges and subranges therebetween. In some embodiments, the glass or glass ceramic composition may contain about 1, 2, 3, 4, 5 or 6 mol % Al2O3.

[0079] In the glass and glass ceramics of this article, Li2O contributes to the formation of a crystalline phase. In some practical compositions, glass or glass ceramics may include about 20 mol % to about 32 mol %Li2O. In some embodiments, glass or glass ceramic compositions may include about 20 to about 32 mol %, about 20 to about 30 mol %, about 20 to about 27 mol %, about 20 to about 25 mol %, about 25 to about 32 mol %, about 25 to about 30 mol %Li2O, and all ranges and sub-ranges therebetween. In some embodiments, glass or glass ceramic compositions may include about 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31 or 32 mol %Li2O.

[0080] As described above, Li2O is generally useful for forming glass ceramics as practiced, but other alkaline oxides tend to reduce the formation of glass ceramics and form aluminosilicate residual glass in glass ceramics. It is found that if the amount of other alkali metal oxides (e.g., Na2O, K2O, Rb2O, Cs2O) is too high, an undesirable amount of residual glass will be present, which can lead to deformation during crystallization and an undesirable microstructure for mechanical properties. The composition of the residual glass can be adjusted to: control the viscosity during crystallization, minimize deformation or undesirable thermal expansion, or control microstructural properties. Therefore, in general, the composition described herein has a low amount of non-lithium alkaline oxides. In some embodiments, the glass or glass ceramic composition may include Li2O (mol%) / R2O (mol%) in a ratio of greater than about 0.85 to 1.0, greater than 0.85 to 0.97, greater than 0.85 to 0.95, 0.86 to 1.0, 0.86 to 0.97, 0.86 to 0.95, 0.87 to 1.0, 0.87 to 0.97, 0.87 to 0.95, 0.88 to 1.0, 0.88 to 0.97, 0.8 ... 0.94 to 1.0, 0.95 to 1.0, 0.96 to 1.0, 0.97 to 1.0, 0.97 to 1.0, 0.98 to 2.0, 0.99 to 3.0, 0.10 to 3.0, 0.11 to 3.0, 0.12 to 3.0, 0.13 to 3.0, 0.14 to 3.0, 0.15 to 3.0, 0.16 to 3.0, 0.17 to 3.0, 0.18 to 3.0, 0.19 to 4.0, 10.2 to 4.0, 11.2 to 4.0, 12.2 to 4.0, 13.2 to 4.0, 14.2 to 4.0, 15.2 to 4.0, 16.2 to 4.0, 17.2 to 4.0, 18.2 to 4.0, 19.2 to 4.0, 20.2 to 4.0, 21.2 to 4.0, 22.2 to 4.0, 23.2 to 4.0, 24.2 to 4.0 In some embodiments, the glass or glass-ceramic composition may include a ratio of Li2O (mol %) / R2O (mol %) greater than or equal to about 0.85, 0.86, 0.87, 0.88, 0.89, 0.9, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, or 0.99.

[0081] Glass and glass ceramic compositions may include P2O5. P2O5 may function as a nucleating agent to produce bulk nucleation. If the concentration of P2O5 is too low, the precursor glass does crystallize, but only at higher temperatures (due to lower viscosity), and produces a weak and often deformed body from the surface inward; however, if the concentration of P2O5 is too high, devitrification after cooling during precursor glass formation may be difficult to control. The composition practiced may include 0.7 to about 2.2 mol%, 0.7 to about 2 mol%, 0.7 to about 1.5 mol%, 0.7 to about 1 mol%, about 1 to about 2.2 mol%, about 1 to about 2 mol%, about 1.5 to about 2.2 mol% P2O5, and all ranges and sub-ranges therebetween. In some embodiments, the glass or glass ceramic composition can include about 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, or 2.2 mol % P2O5.

[0082] In the glass and glass ceramics of this article, it is usually found that ZrO can improve Li by significantly reducing the glass devitrification during forming and reducing the liquidus temperature O-Al O -SiO -P O The stability of glass.Not limited to theory, ZrO The increase of amount increases the amount of alkali metal oxides in the residual glass.Add ZrO It is also possible to help reduce the grain size of the crystal, which helps to form transparent glass ceramics.In some embodiments, glass or glass ceramic composition can include about 1.7 to about 4.5 mol %, about 1.7 to about 4 mol %, about 1.7 to about 3.5 mol %, about 1.7 to about 3 mol %, about 1.7to2.5 mol %, about 2 to about 4.5 mol %, 2 to about 4 mol %, about 2 to about 3.5 mol %, about 2 to about 3 mol %, about 2.5 to about 4.5 mol %, about 2.5to 4 mol %, about 2.5 to about 3.5 mol % ZrO , and all ranges and sub-ranges therebetween. In some embodiments, the glass or glass ceramic composition may include about 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, or 4.5 mol % ZrO2.

[0083] B2O3 is conducive to improving the precursor glass with low melting temperature. In addition, adding B2O3 in the precursor glass (and then adding B2O3 in glass ceramics) helps to achieve interlocking crystal microstructures, and can also improve the anti-destructive properties of glass ceramics. When the boron in the residual glass is not balanced by the charge of alkaline oxides or divalent cation oxides, it will be in a triangular coordination state (or, tricoordinate boron), which opens the structure of the glass. The network around these tricoordinate borons is not as rigid as tetrahedral coordination (or tetracoordinate) boron. Without being limited by theory, it is believed that the precursor glass and glass ceramics containing tricoordinate boron can tolerate a certain degree of deformation before forming cracks. Due to tolerating some deformation, the Vickers indentation crack initiation value is increased. The crushing toughness of the precursor glass and glass ceramics containing tricoordinate boron can also be increased. Without being limited by theory, it is believed that there is boron in the residual glass (and precursor glass) of glass ceramics, which reduces the viscosity of the residual glass (or precursor glass), which helps the growth of lithium silicate crystals (particularly large crystals with high aspect ratio). It is believed that a larger amount of tricoordinate boron (relative to tetracoordinate boron) causes glass-ceramics to exhibit a larger Vickers indentation crack initiation load. In some embodiments, the amount of tricoordinate boron (with all B2O3 percentage) can be about 40% or greater, 50% or greater, 75% or greater, about 85% or greater or even about 95% or greater. Generally speaking, the amount of boron should be controlled to maintain chemical durability and the mechanical strength of the ceramicized bulk glass-ceramics.

[0084] In one or more embodiments, the glasses and glass ceramics herein may contain 0 to about 2 mol % and all ranges and subranges therebetween. In some embodiments, the glass or glass ceramic composition may contain about 0,>0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 or 2 mol % B2O3.

[0085] In one or more embodiments, the glasses and glass-ceramics herein may contain 0 to about 0.5 mol % SnO 2 and function as a fining agent. In some embodiments, the glass or glass ceramic composition can include 0 to about 0.5 mol%, 0 to about 0.4 mol%, 0 to about 0.3 mol%, 0 to about 0.2 mol%, 0 to about 0.1 mol%, about 0.05 to about 0.5 mol%, 0.05 to about 0.4 mol%, 0.05 to about 0.3 mol%, 0.05 to about 0.2 mol%, 0.05 to about 0.1 mol%, about 0.1 to about 0.5 mol%, about 0.1 to about 0.4 mol%, about 0.1 to about 0.3 mol%, about 0.1 to about 0.2 mol%, about 0.2 to about 0.5 mol%, about 0.2 to about 0.4 mol%, about 0.2 to about 0.3 mol%, about 0.3 to about 0.5 mol%, about 0.3 to about 0.4 mol%, about 0.4 to about 0.5 mol%, and all ranges and subranges therebetween. In some embodiments, the glass or glass ceramic composition can include about 0, >0, 0.05, 0.1, 0.2, 0.3, 0.4, or 0.5 mol % SnO2.

[0086] When the amount of transition metal oxides (including but not limited to iron oxides (e.g., Fe2O3), copper oxides (e.g., Cu2O3), chromium oxides (e.g., Cr2O3), and / or molybdenum oxides (e.g., MoO2) is too high, they will affect the color of the glass-ceramic, thereby affecting the transparency of the glass-ceramic. In some embodiments, the glass and / or glass-ceramic composition may contain less than 0.5 mol%, 0.4 mol%, 0.3 mol%, 0.2 mol%, 0.1 mol%, or 0.05 mol% of Fe2O3, Cu2O3, Cr2O3, and / or MoO2, calculated individually or collectively.

[0087] Heat treatment for crystallization / ceramization

[0088] In one or more embodiments, a process for making a glass-ceramic includes: heat treating a precursor glass at one or more predetermined temperatures for one or more predetermined periods of time to induce glass homogenization and crystallization (i.e., nucleation and growth) of one or more crystalline phases (e.g., having one or more compositions, amounts, geometric morphologies, sizes, or size distributions, etc.). In some embodiments, the heat treatment may include: (i) heating the precursor glass to a nucleation temperature (Tn) at a rate of 0.01-50°C / min; (ii) maintaining the crystallizable glass at the nucleation temperature for a first predetermined period of time (t N ) to produce a nucleated crystallizable glass composition; (iii) heating the nucleated crystallizable glass to a crystallization temperature (Tc) at a rate of about 0.01°C / min to about 50°C / min; (iv) maintaining the nucleated crystallizable glass at the crystallization temperature for a second predetermined period of time (tc)C ) to produce the glass ceramic article described herein; and (v) cooling the formed glass ceramic to room temperature. In the aforementioned embodiments, the term "ceramic" or "ceramicization" can be used to refer to steps (iii), (iv) and optionally (v) collectively. In some embodiments, the nucleation temperature can be 500°C to 650°C (e.g., 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, 560°C, 570°C, 580°C, 590°C, 600°C, 610°C, 620°C, 630°C, 640°C, or 650°C) and all ranges and sub-ranges therebetween; and / or the crystallization temperature can be 680°C to 800°C (e.g., 680°C, 690°C, 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C, or 800°C) and all ranges and sub-ranges therebetween. In some embodiments, the first predetermined time of maintaining nucleation temperature can be 1 minute to 6 hours (for example, 1 minute, 5 minutes, 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours or 6 hours), and all ranges and sub-ranges therebetween. In some embodiments, the second predetermined time of maintaining crystallization temperature can be 1 minute to 4 hours (for example, 1 minute, 5 minutes, 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours or 4 hours), and all ranges and sub-ranges therebetween. In some embodiments, crystallization temperature depends on whether transparent or translucent / opaque glass-ceramics are needed. In some embodiments, a crystallization temperature of about 750°C or lower can result in transparent glass-ceramics, and a crystallization temperature higher than about 750°C can result in translucent / opaque glass-ceramics. In some embodiments, the glass may be heated from room temperature to a nucleation temperature of 570°C at a rate of 5°C / min, maintained at the nucleation temperature for 4 hours, then heated to the crystallization temperature at a rate of 5°C / min, and maintained at the crystallization temperature for 1 hour.

[0089] In some embodiments, there may be one of a plurality of additional temperatures kept between nucleation temperature and crystallization temperature.Not limited to theory, this additional temperature keeps reducing the warpage / deformation that residual stress (being measured by optical delay) and ceramicization process induce.Therefore, in some embodiments, after nucleation temperature maintains goods, goods can be heated to one or more intermediate temperatures (wherein, intermediate temperature is between nucleation temperature and crystallization temperature), and keep predetermined time (for example, 10 minutes to 4 hours, and all scopes and sub-ranges therebetween) at described one or more intermediate temperatures, then be heated to crystallization temperature.Embodiment 5 hereinafter verifies the 3 step heat treatment cycles that have intermediate temperature maintenance.

[0090] In some embodiments, once the composition is heated to the nucleation temperature, the composition is not maintained at the nucleation temperature, but as an alternative, continues to be heated to one or more intermediate temperatures until the crystallization temperature is reached (that is, the temperature is not maintained at any one of the intermediate temperature or the nucleation temperature). In some embodiments, the heating rate from room temperature to the nucleation temperature, the heating rate from the nucleation temperature to the intermediate temperature, the heating rate from the intermediate temperature to the crystallization temperature are variable. In the embodiment where there are multiple intermediate temperatures, the heating rate may also change between the individual intermediate temperatures. The following embodiment 6 verifies this type of exemplary thermal treatment scheme. In some embodiments, the heating rate can vary and can be in the range of about 0.01°C / minute to about 50°C / minute, about 0.01°C / minute, about 0.1°C / minute, about 0.5°C / minute, about 1°C / minute, about 2°C / minute, about 3°C / minute, about 4°C / minute, about 5°C / minute, about 10°C / minute, about 15°C / minute, about 20°C / minute, about 25°C / minute, about 30°C / minute, about 40°C / minute, about 45°C / minute, about 50°C / minute, and all ranges and sub-ranges therebetween. In some embodiments, the heating rate can be increased from one heating rate to another heating rate. In other embodiments, the heating rate can be reduced from one heating rate to another heating rate.

[0091] In some embodiments, after the crystallization temperature is maintained, the glass-ceramic article is cooled. In some embodiments, the cooling of the glass-ceramic article to room temperature can be: a constant cooling curvature in a single stage; two stages, respectively having different cooling curvatures; or three or more stages, respectively having different cooling rates. In some embodiments, the glass-ceramic article is cooled from the crystallization temperature at a controlled rate, thereby minimizing the temperature gradient on the article and minimizing the residual stress on the article. Differences in temperature gradients and residual stresses may cause warping of the article during the cooling process. Therefore, cooling is controlled to control the temperature gradient and residual stress, which can also minimize the warping of the glass-ceramic article.

[0092] In some embodiments, for example, Figure 2 As shown, cooling can be performed in two cooling stages. In such an embodiment, in the first cooling stage, the temperature is cooled from T at a first cooling rate. 最大值 (i.e., T C In the second cooling stage, the temperature is cooled from T1 to about room temperature (T 室温 ).like Figure 2 As shown, the first cooling rate is slower than the second cooling rate. During the first stage, the first cooling rate is slow, so that the temperature gradient on the glass ceramic product is minimized. In some embodiments, based on such a temperature (below which the glass ceramic product behaves as a plastic material), the temperature T1 at which the transition from the first cooling stage to the second cooling stage occurs is determined. Not limited to theory, it is believed that the slower cooling rate of the first cooling stage only needs to control the temperature gradient until the glass ceramic product reaches such a temperature, below which it behaves as a plastic material. In some embodiments, temperature T1 can be 450°C to 650°C, and all ranges and sub-ranges therebetween. In some embodiments, the temperature T1 may be less than or equal to 650°C, 640°C, 630°C, 620°C, 610°C, 600°C, 590°C, 580°C, 570°C, 560°C, 550°C, 540°C, 530°C, 520°C, 510°C, 500°C, 490°C, 480°C, 470°C, 460°C, or 450°C. In some embodiments, the temperature drop (T1) in the first cooling stage is less than or equal to 650°C, 640°C, 630°C, 620°C, 610°C, 600°C, 590°C, 580°C, 570°C, 560°C, 550°C, 540°C, 530°C, 520°C, 510°C, 500°C, 490°C, 480°C, 470°C, 460°C, or 450°C. 最大值 -T1) is less than the temperature drop in the second cooling stage (T1-T 室温 Without being limited by theory, it is believed that the temperature gradient established in the first cooling stage has a greater effect (in the form of optical retardation) on the residual stress (and thus warpage) of the glass-ceramic article after reaching room temperature than the temperature gradient established in the second cooling stage. Therefore, in some embodiments, after the controlled cooling of the first cooling stage, the glass-ceramic article can be allowed to cool to room temperature in an uncontrolled cooling environment.

[0093] In some embodiments, for example, Figure 3 As shown, for a total of 3 cooling stages, the cooling cycle can have an intermediate cooling stage between the first cooling stage and the second cooling stage. In such an embodiment, in the first cooling stage, the temperature is cooled from T to T at a first cooling rate. 最大值 (i.e., T C, crystallization temperature) is cooled to T1. In the intermediate cooling stage, the temperature is cooled from T1 to T2 at a second cooling rate. In some embodiments, T2 may be lower than the strain point of the glass ceramic, for example, from about 50°C to about 200°C. In the second stage, the temperature is cooled from T2 to about room temperature (T 室温 ).like Figure 3 As shown, the cooling rate of each stage increases, so that: (i) the first cooling rate during the first cooling stage is less than the second cooling rate during the intermediate cooling stage and the third cooling rate during the second cooling stage; and (ii) the second cooling rate during the intermediate cooling stage is less than the third cooling rate during the second cooling stage. In some embodiments, (i) the temperature drop (T 最大值 -T1) is smaller than the temperature drop in the intermediate cooling stage (T1-T2) and the temperature drop in the second cooling stage (T2-T 室温 ), and (ii) the temperature drop in the intermediate cooling stage (T1-T2) is less than the temperature drop in the second cooling stage (T2-T 室温 ). The intermediate cooling stage enables a faster cooling cycle while still minimizing temperature gradients and residual stresses. In some embodiments, T 最大值 T2 may be about 740°C, T1 may be about 640°C, and T2 may be about 580°C.

[0094] In some embodiments, when there are multiple cooling stages in the cooling cycle, the temperature gradient on the plane of the glass-ceramic article during the first cooling stage can be less than 20°C, less than 19°C, less than 18°C, less than 17°C, less than 16°C, less than 15°C, less than 14°C, less than 13°C, less than 12°C, less than 11°C, less than 10°C, less than 9°C, less than 8°C, less than 7°C, less than 6°C, less than 5°C, less than 4°C, or less than 3°C, and / or the optical retardation at room temperature can be less than 40nm / mm thickness, less than 35nm / mm thickness. The optical retardation may be measured using a photoelastic stress measurement system (e.g., a gray field polarizer GFP-1400 from Stress Photonics, Inc.).

[0095] After the precursor glass is subjected to the above-mentioned heat treatment, the obtained glass-ceramic has one or more crystalline phases and a residual glass phase. In some embodiments, the glass-ceramic contains the following exemplary crystalline phases: lithium disilicate, petalite, β-spodumene solid solution, β-quartz solid solution, lithium metasilicate, omphacite (virgilite), cristobalite, lithium phosphate, baddeleyite and zirconium oxide, and any combination thereof.

[0096] In some embodiments, lithium disilicate is the crystalline phase with the highest weight percentage. Lithium disilicate (Li2Si2O5) is an orthorhombic crystal based on a corrugated sheet of an array of {Si2O5} tetrahedra. The crystals are typically plate-like or lath-like in shape with distinct cleavage planes. Due to their microstructure of randomly oriented interlocking crystals (a crystal structure that forces cracks to propagate through the material via a tortuous path around these crystals), glass-ceramics based on lithium disilicate provide highly desirable mechanical properties, including high bulk strength and crushing toughness. In some embodiments, the weight percentage of the lithium disilicate crystalline phase in the glass-ceramic composition can be in the range of about 20 to about 60 weight %, about 20 to about 55 weight %, about 20 to about 50 weight %, about 20 to about 45 weight %, about 20 to about 40 weight %, about 20 to about 35 weight %, about 20 to about 30 weight %, about 20 to about 25 weight %, about 25 to about 60 weight %, about 25 to about 55 weight %, about 25 to about 50 weight %, about 25 to about 45 weight %, about 25 to about 40 weight %, about 25 to about 35 weight %, about 25 to about 30 weight %, about 20 to about 25 weight %, about 25 to about 60 weight %, about 25 to about 55 weight %, about 25 to about 50 weight %, about 25 to about 45 weight %, about 25 to about 40 weight %, about 25 to about 35 weight %, about 25 to about 30 weight %, about 30 to about 60 weight %. %, about 30 to about 50 wt %, about 30 to about 45 wt %, about 30 to about 40 wt %, about 30 to about 35 wt %, about 35 to about 60 wt %, about 35 to about 55 wt %, about 35 to about 50 wt %, about 35 to about 45 wt %, about 35 to about 40 wt %, about 40 to about 60 wt %, about 40 to about 55 wt %, about 40 to about 50 wt %, about 40 to about 45 wt %, about 45 to about 60 wt %, about 45 to about 55 wt %, about 45 to about 50 wt %, about 50 to about 60 wt %, about 50 to about 55 wt % or about 55 to about 60 wt %. In some embodiments, the glass-ceramic has 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, or 60 weight percent lithium disilicate crystalline phase.

[0097] In some embodiments, petalite is the crystalline phase with the highest weight percentage. 10) is a monoclinic crystal with a three-dimensional framework structure, with a layered structure, folded Si2O5 layers connected by Li and Al tetrahedra. Li is coordinated tetrahedrally with oxygen. The mineral petalite is a lithium source and is used as a low thermal expansion phase to improve the thermal downshock resistance of glass ceramics or ceramic parts. In addition, glass ceramic products based on petalite can be chemically strengthened in a salt bath, in which process Na + (and / or K + ) replaces Li in the petalite structure +, which results in surface compression and strengthening. In some embodiments, the weight percentage of the petalite crystalline phase in the glass-ceramic composition can be in the range of about 20 to about 70 weight %, about 20 to about 65 weight %, about 20 to about 60 weight %, about 20 to about 55 weight %, about 20 to about 50 weight %, about 20 to about 45 weight %, about 20 to about 40 weight %, about 20 to about 35 weight %, about 20 to about 30 weight %, about 20 to about 25 weight %, about 25 to about 7 ...5 weight %, about 20 to about 35 weight %, about 20 to about 35 weight %, about 20 to about 35 weight %, about 20 to about 35 weight %, about 20 to about 35 weight %, about 20 to about 35 weight %, about 20 %, about 25 to about 65 wt %, about 25 to about 60 wt %, about 25 to about 55 wt %, about 25 to about 50 wt %, about 25 to about 45 wt %, about 25 to about 40 wt %, about 25 to about 35 wt %, about 25 to about 30 wt %, about 30 to about 70 wt %, about 30 to about 65 wt %, about 30 to about 60 wt %, about 30 to about 55 wt %, about 30 to about 50 wt %, about 30 to about 45 wt %, about 30 to about 40 wt %, %, about 30 to about 35 wt %, about 35 to about 70 wt %, about 35 to about 65 wt %, about 35 to about 60 wt %, about 35 to about 55 wt %, about 35 to about 50 wt %, about 35 to about 45 wt %, about 35 to about 40 wt %, about 40 to about 70 wt %, about 40 to about 65 wt %, about 40 to about 60 wt %, about 40 to about 55 wt %, about 40 to about 50 wt %, about 40 ...45 to about %, about 45 to about 65 wt %, about 45 to about 60 wt %, about 45 to about 55 wt %, about 45 to about 50 wt %, about 50 to about 70 wt %, about 50 to about 65 wt %, about 50 to about 60 wt %, about 50 to about 55 wt %, about 55 to about 70 wt %, about 55 to about 65 wt %, about 55 to about 60 wt %, about 60 to about 70 wt %, about 60 to about 65 wt %, or about 65 to about 70 wt %. In some embodiments, the glass-ceramic has about 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, or 70 weight percent petalite crystalline phase.

[0098] In some embodiments, crystalline phases other than lithium disilicate and petalite comprise less than 5 wt%, less than 4 wt%, less than 3 wt%, less than 2 wt%, or less than 1 wt% of the total wt% of the glass-ceramic article.

[0099] In some embodiments, the glass-ceramic has a residual glass content of about 5 to about 50 wt %, about 5 to about 45 wt %, about 5 to about 40 wt %, about 5 to about 35 wt %, about 5 to about 30 wt %, about 5 to about 25 wt %, about 5 to about 20 wt %, about 5 to about 15 wt %, about 5 to about 10 wt %, about 10 to about 50 wt %, about 10 to about 45 wt %, about 10 to about 40 wt %, about 10 to about 35 wt %, about 10 to about 30 wt %, about 10 ...10 to about 2 %, about 15 to about 50 wt %, about 15 to about 45 wt %, about 15 to about 40 wt %, about 15 to about 35 wt %, about 15 to about 30 wt %, about 15 to about 25 wt %, about 15 to about 20 wt %, about 20 to about 50 wt %, about 20 to about 45 wt %, about 20 to about 40 wt %, about 20 to about 35 wt %, about 20 to about 30 wt %, about 20 to about 25 wt %, about 25 to about 30 wt %, and all ranges and subranges therebetween. In some embodiments, the residual glass content may be less than or equal to 50, 45, 40, 35, 30, 25, 20, 19, 18, 17, 16, 15, 14, 13, 12, 11, 10, 9, 8, 7, 6, 5, 4, 3, 2, or 1 wt %.

[0100] In some embodiments, the glass-ceramic can have a crystalline weight % in the range of greater than 20 wt % to 100 wt %, greater than 20 wt % to 90 wt %, greater than 20 wt % to 80 wt %, greater than 20 wt % to 70 wt %, 30 wt % to 100 wt %, 30 wt % to 90 wt %, 30 wt % to 80 wt %, 30 wt % to 70 wt %, 40 wt % to 100 wt %, 40 wt % to 90 wt %, 40 wt % to 80 wt %, 40 wt % to 70 wt %, 50 wt % to 100 wt %, 50 wt % to 90 wt %, 50 wt % to 80 wt %, 50 wt % to 70 wt %, and all ranges and sub-ranges therebetween. In some embodiments, the inner region has a crystal weight percentage greater than 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, or 90% by weight.

[0101] The grain size of the crystal in the crystalline phase is a factor affecting the transparency of glass-ceramic. In some embodiments, the longest dimension of crystal grain is as follows: about 5nm to about 150nm, about 5nm to about 125nm, about 5nm to about 100nm, about 5nm to about 75nm, about 5nm to about 50nm, about 25nm to about 150nm, about 25nm to about 125nm, about 25nm to about 100nm, about 25nm to about 75nm, about 50nm to about 150nm, about 50nm to about 125nm, about 50nm to about 100nm, and all scopes and sub-ranges therebetween. In some embodiments, the longest dimension of crystal grain is less than 150nm, less than 125nm, less than 100nm, less than 75nm, less than 50nm or less than 25nm. Scanning electron microscope (SEM) is used to measure the longest dimension of crystal grain.

[0102] In some embodiments, the phase combination and heat treatment conditions are selected to produce a glass-ceramic article with suitable optical properties (e.g., transparency and low haze) for use as cover glass for mobile electronic devices. In some embodiments, for a glass-ceramic article with a thickness of 1 mm, the glass-ceramic article is transparent for light in the wavelength range of 450 nm to 600 nm, having a transmittance of 85% or more, 86% or more, 87% or more, 88% or more, 89% or more, 90% or more, 91% or more, 92% or more, 93% or more (including surface reflection losses). In other embodiments, the glass-ceramic may be translucent in the wavelength range of 450 nm to 600 nm. In some embodiments, for a glass-ceramic article with a thickness of 1 mm, the translucent glass-ceramic may have an average transmittance of about 20% to less than about 85% for light in the wavelength range of about 450 nm to about 800 nm. In some embodiments, the glass-ceramic article has a haze of less than 0.2, 0.19, 0.18, 0.17, 0.16, 0.15, 0.14, 0.13, 0.12, 0.11, or 0.1.

[0103] The following equation (2) estimates the haze of the glass-ceramic article based on the nucleation temperature (TN), the nucleation retention time (tN), the crystallization temperature (TC), and the crystallization retention time (tC).

[0104] Estimated haze = 103–0.260T N +0.000203(T N ) 2 –7.96t N +0.1532(t N ) 2 –0.019T C –0.000008(T C )2 –10.03t C +0.00597T N *t N +0.00463t N *T C +0.01342T C *t C (2)

[0106] In some embodiments, the nucleation temperature (TN), nucleation hold time (tN), crystallization temperature (TC), and crystallization hold time (tC) of the heat treatment cycle can be selected based on the estimated haze provided by equation (2) so that the estimated haze is less than 0.2, 0.19, 0.18, 0.17, 0.16, 0.15, 0.14, 0.13, 0.12, 0.11, or 0.1. In some embodiments, the heat treatment can include: (i) heating the precursor glass to the nucleation temperature (Tn) at a rate of 0.01-50°C / min; (ii) maintaining the crystallizable glass at the nucleation temperature for a first predetermined period of time (t N ) to produce a nucleated crystallizable glass composition; (iii) heating the nucleated crystallizable glass to a crystallization temperature (Tc) at a rate of about 0.01°C / min to about 50°C / min; (iv) maintaining the nucleated crystallizable glass at the crystallization temperature for a second predetermined period of time (tc) C ) to produce the glass-ceramic article described herein; and (v) cooling the formed glass-ceramic to room temperature such that the value of equation (2) is less than 0.2, 0.19, 0.18, 0.17, 0.16, 0.15, 0.14, 0.13, 0.12, 0.11 or 0.1.

[0107] Ion Exchange

[0108] In some embodiments, one or more ion exchange techniques can be used to chemically strengthen the glass ceramic article. In these embodiments, one or more surfaces of such glass ceramic articles can be passed through one or more ion exchange media (e.g., molten salt baths) having a specific composition and temperature for a specific period of time, so that the one or more surfaces have a compressive stress layer. In some embodiments, the ion exchange medium is a molten bath, and the ions (e.g., alkali metal ions) contained therein are greater than the ions (e.g., alkali metal ions) present in the glass ceramic article, wherein the larger ions from the molten bath are exchanged with the smaller ions in the glass ceramic article, giving compressive stress in the glass ceramic article, thereby increasing the strength of the glass ceramic article.

[0109] In some embodiments, a single-step ion exchange process can be used, while in other embodiments, a multi-step ion exchange process can be used. In some embodiments, for both single-step and multi-step ion exchange processes, the ion exchange medium (e.g., molten bath) can contain 100% by weight sodium-containing salt (e.g., NaNO3) or can contain a mixed salt bath (e.g., a combination of sodium-containing salt (e.g., NaNO3) and potassium-containing salt (e.g., KNO3)). In some embodiments, when the molten salt bath contains a sodium-containing salt (e.g., NaNO3) in the following ranges: 3 wt% to 100 wt%, 3 wt% to 95 wt%, 3 wt% to 90 wt%, 3 wt% to 85 wt%, 3 wt% to 80 wt%, 3 wt% to 75 wt%, 5 wt% to 100 wt%, 5 wt% to 95 wt%, 5 wt% to 90 wt%, 5 wt% to 85 wt%, 5 wt% to 80 wt%, 5 wt% to 75 wt%, 10 wt% to 100 wt%, 10 wt% to 95 wt%, 10 wt% to 9 % to 80 wt %, 30 wt % to 75 wt %, and all ranges and subranges therebetween. In some embodiments, other sodium and potassium salts may be used in the ion exchange solution, for example, sodium or potassium nitrite, sodium or potassium phosphate, or sodium or potassium sulfate.

[0110] After ion exchange has been performed, it is understood that the composition at the surface of the glass-ceramic may be different from the composition of the as-formed glass-ceramic (i.e., the glass-ceramic before undergoing the ion exchange process). This is due to the presence of one type of alkali metal ion (e.g., Li + Or Na + ) are replaced by larger alkali metal ions (e.g., Na + or K + However, in an embodiment, the composition of the glass-ceramic at or near the center of the depth of the glass-ceramic will still have the composition of the just-formed glass-ceramic.

[0111] Final Product

[0112] The glass-ceramic articles disclosed herein can be integrated into another article, such as an article with a display screen (or display article) (e.g., consumer electronics, including mobile phones, tablets, computers, navigation systems, and wearable devices (e.g., watches), etc.), a building article, a transportation article (e.g., a vehicle, a train, an aircraft, a marine craft, etc., such as an interior display cover, a window, or a windshield), an electrical article, or any article requiring partial transparency, scratch resistance, abrasion resistance, or a combination thereof. Exemplary articles incorporating any of the reinforced glass-ceramic articles disclosed herein are as follows: Figure 4A and 4B Specifically, Figure 4A and 4B A consumer electronic device 200 is shown, comprising: a housing 202 having a front surface 204, a rear surface 206, and a side surface 208; an electronic assembly (not shown) at least partially or completely within the housing and including at least a controller, a memory, and a display 210 located at or adjacent to the front surface of the housing; and a cover substrate 212 located at or above the front surface of the housing so that it is located above the display. In some embodiments, at least one of the cover substrate 212 or a portion of the housing 202 may include any of the strengthened glass-ceramic articles disclosed herein.

[0113] Example

[0114] Various embodiments are further illustrated by the following examples.

[0115] Example 1

[0116] A precursor glass sample having a thickness of 0.8 mm was formed having the composition of Composition 3 listed in Table 1 above. The sample was heated from room temperature to approximately 560°C at a heating rate of 5°C / min and held for 4 hours. Then, the sample was heated to 730°C at a heating rate of 5°C / min and held for 1 hour to form a glass ceramic article. The glass ceramic sample was then ion exchanged in a molten salt bath containing 95 wt% NaNO3 and 5 wt% KNO3 at 470°C. The first sample was ion exchanged for 2 hours, the second sample was ion exchanged for 4 hours, the third sample was ion exchanged for 7 hours, the fourth sample was ion exchanged for 16 hours, and the fifth sample was ion exchanged for 24 hours. The stress distribution of each sample is shown in FIG. Figure 5 As shown, CT is shown as positive stress, and CS is shown as negative stress. The sample ion-exchanged for 16 hours has a maximum CT of about 135 MPa, about 37 J / m 2 of stored tensile energy and broke into 2 fragments when subjected to fragmentation testing.

[0117] Example 2

[0118] Precursor glass samples having a thickness of 0.8 mm were formed, having the composition of Composition 3 listed in Table 1 and the composition of Comparative Example 1 listed in Table 2 below.

[0119] Table 2

[0120]

[0121]

[0122] Then, the glass sample was heated from room temperature to approximately 560°C at a heating rate of 5°C / min and maintained for 4 hours. Then, the sample was heated to 730°C at a heating rate of 5°C / min and maintained for 1 hour to form a glass ceramic product. Then, the glass ceramic sample was ion exchanged in a molten salt bath containing 95 wt% NaNO3 and 5 wt% KNO3 at 470°C. The first group of samples were ion exchanged for 2 hours, the second group of samples were ion exchanged for 4 hours, the third group of samples were ion exchanged for 7 hours, the fourth group of samples were ion exchanged for 16 hours, and the fifth group of samples (composition 3 only) were ion exchanged for 24 hours. Figure 6 A graph showing the relationship between the maximum CT (y-axis) and the ion exchange time (x-axis) for each sample is shown. The glass-ceramic article made from composition 3 achieved a maximum CT of approximately 135 MPa, while the glass-ceramic article made from comparative example composition 1 did not achieve the desired maximum CT of greater than 90 MPa (it reached about 70 MPa). Without being limited by theory, it is believed that the higher mol % ZrO2 in composition 3 allows the glass-ceramic made from composition 3 to achieve a higher CT. Without being limited by theory, it is believed that a ZrO2 concentration of 1.7 mol % or higher results in a glass-ceramic article having a maximum CT of greater than 90 MPa and a maximum CT of greater than 22 J / m 2 of stored tensile energy.

[0123] Example 3

[0124] A precursor glass sample having a thickness of 0.8 mm was formed having the composition of Composition 1 listed in Table 1 above. The sample was heated from room temperature to approximately 570° C. at a heating rate of 5° C. / min and held for 4 hours. The sample was then heated to 740° C. at a heating rate of 5° C. / min and held for 1 hour to form a glass ceramic article. The glass ceramic article was cooled to room temperature at a cooling rate of 5° C. / min. The phase assembly of the glass ceramic article was approximately 12+ / -2 wt.% residual glass; 44+ / -2 wt.% petalite crystalline phase; and 44+ / -2 wt.% lithium disilicate crystalline phase. The sum of all other crystalline phases (e.g., other than petalite and lithium disilicate) was less than 2 wt.%. Figure 7 is the result of X-ray diffraction (XRD), and Rietveld analysis is performed on the phase set. Figure 8As shown, the glass ceramic has a transmittance of 90% at visible wavelengths.

[0125] Example 4

[0126] A precursor glass sample having a thickness of 0.8 was formed having the composition of Composition 1 listed in Table 1 above. The sample was subjected to the heat treatment cycle and the phase assembly and haze as shown in Table 3 below. It can be seen that the heat treatment cycle affects the phase assembly and haze. Specifically, when the weight % of the crystalline phase other than lithium disilicate and petalite is less than 2 weight % of the glass ceramic article, the haze is less than 0.2.

[0127] Table 3

[0128]

[0129]

[0130]

[0131] Example 5

[0132] A precursor glass sample having a thickness of 0.8 was formed having the composition of Composition 1 listed in Table 1 above. The sample was subjected to the heat treatment cycle shown in Table 4 below, and the phase assembly is shown in Table 5 below. The heat treatment cycle in this embodiment differs from the heat treatment cycle of Example 4 in that it is a 3-step heating cycle instead of a 2-step heating cycle. Specifically, the sample is maintained at an intermediate temperature, wherein the intermediate temperature is greater than the nucleation temperature and less than the crystallization temperature. This example demonstrates that a desired phase assembly (wherein the weight % of crystalline phases other than lithium disilicate and petalite is less than 2 weight % of the glass ceramic article) can be achieved by replacing a 2-step heat treatment cycle with a 3-step heat treatment cycle.

[0133] Table 4

[0134]

[0135]

[0136] Table 5

[0137]

[0138] Example 6

[0139] A precursor glass sample having a thickness of 0.8 was formed, having the composition of Composition 1 listed in Table 1 above. The sample was subjected to the heat treatment cycle shown in Table 6 below, and the phase assembly is shown in Table 7 below. The heat treatment cycle of this example differs from that of Example 4 in that the sample is not held at the nucleation temperature, but is heated to various temperatures at varying heating rates until the crystallization temperature is reached. This example demonstrates that the desired phase assembly (wherein the weight % of crystalline phases other than lithium disilicate and petalite is less than 2 weight % of the glass ceramic article) can be achieved by this alternative heat treatment cycle.

[0140] Table 6

[0141]

[0142]

[0143] Table 7

[0144]

[0145] It is obvious to those skilled in the art that various modifications and variations can be made without departing from the scope or spirit of the invention. For example, various elements of the present disclosure can be combined according to the following embodiments.

[0146] Embodiment 1: A glass ceramic product comprising:

[0147] a first surface;

[0148] a second surface opposite to the first surface;

[0149] one or more crystalline phases;

[0150] Residual glass phase;

[0151] a compressive stress layer extending from the first surface to a depth of compression (DOC);

[0152] Maximum central tension greater than 70MPa;

[0153] More than 22J / m 2 The stored tensile energy

[0154] A crush toughness greater than 1.0 MPa√m, wherein the crush toughness is measured on a glass-ceramic having a composition and phase assembly equivalent to the composition and phase assembly at the center of the glass-ceramic article; and

[0155] The haze is less than 0.2.

[0156] Embodiment 2: The glass-ceramic article of Embodiment 1 further comprises a Young's modulus greater than 95 GPa, wherein the Young's modulus is measured on a glass-ceramic having a composition and phase assembly equivalent to the composition and phase assembly at the center of the glass-ceramic article.

[0157] Embodiment 3: The glass-ceramic article of any of the preceding embodiments, wherein the crushing toughness is greater than 1.0 MPa√m to 2.0 MPa√m.

[0158] Embodiment 4: A glass ceramic product comprising:

[0159] a first surface;

[0160] a second surface opposite to the first surface;

[0161] one or more crystalline phases;

[0162] Residual glass phase;

[0163] a compressive stress layer extending from the first surface to a depth of compression (DOC);

[0164] Maximum central tension greater than 70MPa;

[0165] More than 22J / m 2 The stored tensile energy

[0166] A Young's modulus greater than 95 GPa, wherein the Young's modulus is measured on a glass-ceramic having a composition and phase assembly equivalent to the composition and phase assembly at the center of the glass-ceramic article; and

[0167] The haze is less than 0.2.

[0168] Embodiment 5: The glass-ceramic article of Embodiment 4, wherein the Young's modulus is greater than 95 GPa to 110 GPa.

[0169] Embodiment 6: The glass-ceramic article of any of the preceding embodiments, wherein the ratio of Li2O (mol %) / R2O (mol %) is greater than 0.85, wherein R2O is the sum of alkali metal oxides.

[0170] Embodiment 7: The glass-ceramic article of Embodiment 6, further comprising 1.7 mol % to 4.5 mol % ZrO2.

[0171] Embodiment 8: A glass ceramic product comprising:

[0172] a first surface;

[0173] a second surface opposite to the first surface;

[0174] one or more crystalline phases;

[0175] Residual glass phase;

[0176] a compressive stress layer extending from the first surface to a depth of compression (DOC);

[0177] Maximum central tension greater than 70MPa;

[0178] More than 22J / m 2 The stored tensile energy

[0179] 1.7 mol % to 4.5 mol % ZrO2; and

[0180] The ratio of Li2O (mol %) / R2O (mol %) is greater than 0.85, wherein R2O is the sum of alkali metal oxides.

[0181] Embodiment 9: The glass-ceramic article of any of the preceding embodiments, wherein the residual glass phase is less than or equal to 50% by weight of the glass-ceramic article.

[0182] Embodiment 10: The glass-ceramic article of any of the preceding embodiments, wherein the one or more crystalline phases comprises petalite.

[0183] Embodiment 11: The glass-ceramic article of any of the preceding embodiments, wherein the one or more crystalline phases comprise lithium disilicate.

[0184] Embodiment 12: The glass-ceramic article of any of the preceding embodiments, wherein the sum of crystalline phases other than lithium disilicate and petalite is less than 2% by weight of the glass-ceramic article.

[0185] Embodiment 13: The glass-ceramic article of any of the preceding embodiments, wherein the glass-ceramic article is transparent and has a transmittance of at least 85% for light in the wavelength range of 450 nm to 800 nm for a thickness of 1 mm.

[0186] Embodiment 14: The glass-ceramic article of any of the preceding embodiments, wherein the glass-ceramic article breaks into less than 5 fragments when subjected to a fragment test.

[0187] Embodiment 15: The glass-ceramic article of any of the preceding embodiments, wherein the maximum central tension is greater than 90 MPa to 180 MPa.

[0188] Embodiment 16: The glass-ceramic article of any of the preceding embodiments, wherein the stored tensile energy is greater than 22 J / m 2 Up to 60J / m 2 .

[0189] Embodiment 17: The glass-ceramic article of Embodiment 1, further comprising grains having a longest dimension of 150 nm or less.

[0190] Embodiment 18: A consumer electronic product comprising:

[0191] a housing including a front surface, a back surface, and a side surface;

[0192] an electronic assembly at least partially located within the housing, the electronic assembly including at least a controller, a memory, and a display, the display being located at or adjacent to the front surface of the housing; and

[0193] a cover substrate disposed above the display,

[0194] Wherein, at least one of a portion of the outer shell or the cover glass comprises the glass-ceramic product as described in any of the above embodiments.

[0195] Embodiment 19: A method of forming a glass-ceramic article, the method comprising:

[0196] heating the glass composition to a nucleation temperature to produce a nucleated crystallizable glass composition;

[0197] heating the nucleated crystallizable glass composition to a crystallization temperature; and

[0198] maintaining the crystallization temperature for a predetermined period of time to produce a glass-ceramic article,

[0199] Among them, glass ceramic products include:

[0200] A crushing toughness greater than 1.0 MPa√m; and

[0201] The haze is less than 0.2.

[0202] Embodiment 20: The method of Embodiment 19, further comprising: maintaining the nucleation temperature for a predetermined period of time to produce a nucleated crystallizable glass composition.

[0203] Embodiment 21: The method of embodiment 20, wherein the nucleation temperature is maintained for a period of time ranging from 1 minute to 6 hours.

[0204] Embodiment 22: The method of Embodiment 19, wherein the glass composition is not maintained at a nucleation temperature.

[0205] Embodiment 23: The method of any one of embodiments 19-22, further comprising:

[0206] heating the nucleated crystallizable glass composition to an intermediate temperature, wherein the intermediate temperature is greater than the nucleation temperature and less than the crystallization temperature; and

[0207] The nucleated crystallizable glass composition is heated from the intermediate temperature to a crystallization temperature.

[0208] Embodiment 24: The method of embodiment 23, further comprising: maintaining the intermediate temperature for a predetermined period of time.

[0209] Embodiment 25: The method of Embodiment 23 or 24, wherein a heating rate for heating the nucleated crystallizable glass composition from the nucleation temperature to the intermediate temperature is different from a heating rate for heating the nucleated crystallizable glass composition from the intermediate temperature to the crystallization temperature.

[0210] Embodiment 26: The method of Embodiment 25, wherein the nucleated crystallizable glass composition is not maintained at an intermediate temperature.

[0211] Embodiment 27: The method of any one of embodiments 19-26, further comprising:

[0212] Subjecting the glass-ceramic article to an ion exchange treatment to produce a compressive stress layer extending from a first surface of the glass-ceramic article to a depth of compression (DOC), wherein after the ion exchange treatment, the glass-ceramic article has a maximum central tension greater than 70 MPa and a stress greater than 22 J / m 2 of stored tensile energy.

[0213] Embodiment 28: The method of any of Embodiments 19-27, wherein the nucleation temperature is 550°C to 650°C.

[0214] Embodiment 29: The method of any one of Embodiments 19-28, wherein heating to the nucleation temperature comprises heating from room temperature to the nucleation temperature at a heating rate of 0.01° C. / min to 50° C. / min.

[0215] Embodiment 30: The method of any one of Embodiments 19-29, wherein the crystallization temperature is 680°C to 800°C.

[0216] Embodiment 31: The method of any one of Embodiments 19-30, wherein the crystallization temperature is maintained for a predetermined period of time of 1 minute to 4 hours.

[0217] Embodiment 32: The method of any of Embodiments 19-31, wherein heating to the crystallization temperature comprises heating from the nucleation temperature to the crystallization temperature at a heating rate of 0.01°C / min to 50°C / min.

[0218] Embodiment 33: A method as in any one of embodiments 19-32, further comprising:

[0219] In a first cooling stage, cooling the glass-ceramic article from a crystallization temperature to a first temperature at a first cooling rate; and

[0220] In a second cooling stage, cooling the glass-ceramic article from the first temperature to a second temperature at a second cooling rate;

[0221] The first cooling rate is slower than the second cooling rate.

[0222] Embodiment 34: The method of any one of embodiments 19-32, further comprising:

[0223] In a first cooling stage, the glass-ceramic article is cooled from a crystallization temperature to a first temperature at a first cooling rate;

[0224] In an intermediate cooling stage, cooling the glass-ceramic article from a first temperature to a second temperature at a second cooling rate;

[0225] In a second cooling stage, cooling the glass-ceramic article from the second temperature to a third temperature at a third cooling rate;

[0226] wherein (i) the first cooling rate is slower than the second cooling rate and the third cooling rate, and (ii) the second cooling rate is slower than the third cooling rate.

[0227] Embodiment 35: The method of any one of Embodiments 19-34, wherein the optical retardation of the glass-ceramic is less than 15 nm / mm thickness.

[0228] Embodiment 36: A method of forming a glass-ceramic article, the method comprising:

[0229] The glass composition is heated to a nucleation temperature (T N );

[0230] Maintaining the nucleation temperature for a first predetermined period of time (t N ) to produce a nucleated crystallizable glass composition;

[0231] The nucleated crystallizable glass composition is heated to a crystallization temperature (T C );as well as

[0232] Maintaining the crystallization temperature for a second predetermined period of time (t C ) to produce glass ceramic products,

[0233] Among them, (103–0.260T N +0.000203(T N ) 2 –7.96t N +0.1532(tN ) 2 –0.019T C –0.000008(T C ) 2 –10.03t C +0.00597T N *t N +0.00463t N *T C +0.01342T C *t C )<0.2.

[0234] Embodiment 37: A method for controlling the haze of a glass-ceramic article, the method comprising:

[0235] The nucleation temperature (T N ), the first predetermined time period (t N ), crystallization temperature (T C ) and a second predetermined time period (t C ) is selected so that (103–0.260T N +0.000203(T N ) 2 –7.96t N +0.1532(t N ) 2 –0.019T C –0.000008(T C ) 2 –10.03t C +0.00597T N *t N +0.00463t N *T C +0.01342T C *t C )<0.2.

[0236] Embodiment 38: The method of embodiment 37, further comprising:

[0237] The glass composition is heated to a nucleation temperature (T N );

[0238] Maintaining the nucleation temperature for the first predetermined period of time (t N ) to produce a nucleated crystallizable glass composition;

[0239] The nucleated crystallizable glass composition is heated to a crystallization temperature (T C );as well as

[0240] Maintaining the crystallization temperature for the second predetermined period of time (t C ) to produce glass ceramic products.

[0241] This application also relates to the following items.

[0242] 1. A glass ceramic product comprising:

[0243] a first surface;

[0244] a second surface opposite to the first surface;

[0245] one or more crystalline phases;

[0246] Residual glass phase;

[0247] a compressive stress layer extending from the first surface to a depth of compression (DOC);

[0248] Maximum central tension greater than 70MPa;

[0249] More than 22J / m 2 The stored tensile energy

[0250] And any one or more of the following:

[0251] (a) a crush toughness greater than 1.0 MPa√m, wherein the crush toughness is measured on a glass-ceramic having a composition and phase assembly equivalent to the composition and phase assembly at the center of the glass-ceramic article; and a haze less than 0.2;

[0252] (b) a Young's modulus greater than 95 GPa, wherein the Young's modulus is measured on a glass-ceramic having a composition and phase assembly equivalent to the composition and phase assembly at the center of the glass-ceramic article; and a haze less than 0.2; and

[0253] (c) ZrO2 is 1.7 mol% to 4.5 mol%, and the ratio of Li2O (mol%) / R2O (mol%) is greater than 0.85, wherein R2O is the sum of alkali metal oxides.

[0254] 2. The glass-ceramic article of item 1, wherein the residual glass phase is less than or equal to 50% by weight of the glass-ceramic article.

[0255] 3. The glass-ceramic article of any of the preceding clauses, wherein the one or more crystalline phases comprise petalite.

[0256] 4. The glass-ceramic article of any of the preceding clauses, wherein the one or more crystalline phases comprise lithium disilicate.

[0257] 5. The glass-ceramic article according to any of the preceding clauses, wherein the sum of crystalline phases other than lithium disilicate and petalite is less than 2% by weight of the glass-ceramic article.

[0258] 6. The glass-ceramic article according to any of the preceding clauses, wherein the glass-ceramic article is transparent and has a transmittance of at least 85% for light in the wavelength range of 450 nm to 800 nm for a thickness of 1 mm.

[0259] 7. The glass-ceramic article as described in any of the preceding items, wherein when subjected to a fragment test, the glass-ceramic article breaks into less than 5 fragments.

[0260] 8. The glass-ceramic article according to any of the preceding items, wherein the maximum central tension is greater than 90 MPa to 180 MPa.

[0261] 9. The glass-ceramic article according to any of the preceding items, wherein the stored tensile energy is greater than 22 J / m 2 Up to 60J / m 2 .

[0262] 10. The glass-ceramic article of item 1, further comprising grains having a longest dimension of 150 nm or less.

[0263] 11. A consumer electronic product comprising:

[0264] a housing including a front surface, a back surface, and a side surface;

[0265] an electronic assembly at least partially located within the housing, the electronic assembly including at least a controller, a memory, and a display, the display being located at or adjacent to the front surface of the housing; and

[0266] a cover substrate disposed above the display,

[0267] Wherein, at least one of a portion of the outer shell or the covering substrate comprises the glass ceramic product as described in any of the preceding items.

[0268] 12. A method of forming a glass-ceramic article, the method comprising:

[0269] The glass composition is heated to a nucleation temperature (T N ) to produce a nucleated crystallizable glass composition;

[0270] The nucleated crystallizable glass composition is heated to a crystallization temperature (T C );as well as

[0271] Maintain the crystallization temperature for a predetermined period of time (tC ) to produce glass ceramic products,

[0272] Among them, glass ceramic products include:

[0273] A crushing toughness greater than 1.0 MPa√m; and

[0274] The haze is less than 0.2.

[0275] 13. The method of item 12, further comprising: maintaining the nucleation temperature for a predetermined period of time to produce a nucleated crystallizable glass composition.

[0276] 14. The method of item 13, wherein the nucleation temperature is maintained for a period of time ranging from 1 minute to 6 hours.

[0277] 15. The method of claim 12, wherein the glass composition is not maintained at a nucleation temperature.

[0278] 16. The method according to any one of items 12 to 15, further comprising:

[0279] heating the nucleated crystallizable glass composition to an intermediate temperature, wherein the intermediate temperature is greater than the nucleation temperature and less than the crystallization temperature; and

[0280] The nucleated crystallizable glass composition is heated from the intermediate temperature to a crystallization temperature.

[0281] 17. The method of item 16, further comprising: maintaining the intermediate temperature for a predetermined period of time.

[0282] 18. The method of item 16 or 17, wherein a heating rate of heating the nucleated crystallizable glass composition from the nucleation temperature to the intermediate temperature is different from a heating rate of heating the nucleated crystallizable glass composition from the intermediate temperature to the crystallization temperature.

[0283] 19. The method of clause 18, wherein the nucleated crystallizable glass composition is not maintained at an intermediate temperature.

[0284] 20. The method according to any one of items 12 to 19, further comprising:

[0285] Subjecting the glass-ceramic article to an ion exchange treatment to produce a compressive stress layer extending from a first surface of the glass-ceramic article to a depth of compression (DOC), wherein after the ion exchange treatment, the glass-ceramic article has a maximum central tension greater than 70 MPa and a stress greater than 22 J / m 2 of stored tensile energy.

[0286] 21. The method of any one of items 12-20, wherein the nucleation temperature is 550°C to 650°C.

[0287] 22. The method of any one of items 12-21, wherein heating to the nucleation temperature comprises heating from room temperature to the nucleation temperature at a heating rate of 0.01°C / min to 50°C / min.

[0288] 23. The method of any one of items 12-22, wherein the crystallization temperature is 680°C to 800°C.

[0289] 24. The method of any one of items 12-23, wherein the predetermined period of time for which the crystallization temperature is maintained is from 1 minute to 4 hours.

[0290] 25. The method of any one of items 12-24, wherein heating to the crystallization temperature comprises heating from the nucleation temperature to the crystallization temperature at a heating rate of 0.01°C / min to 50°C / min.

[0291] 26. The method according to any one of items 12 to 25, further comprising:

[0292] In a first cooling stage, cooling the glass-ceramic article from a crystallization temperature to a first temperature at a first cooling rate; and

[0293] In a second cooling stage, cooling the glass-ceramic article from the first temperature to a second temperature at a second cooling rate;

[0294] The first cooling rate is slower than the second cooling rate.

[0295] 27. The method according to any one of items 12 to 26, further comprising:

[0296] In a first cooling stage, the glass-ceramic article is cooled from a crystallization temperature to a first temperature at a first cooling rate;

[0297] In an intermediate cooling stage, cooling the glass-ceramic article from a first temperature to a second temperature at a second cooling rate;

[0298] In a second cooling stage, cooling the glass-ceramic article from the second temperature to a third temperature at a third cooling rate;

[0299] wherein (i) the first cooling rate is slower than the second cooling rate and the third cooling rate, and (ii) the second cooling rate is slower than the third cooling rate.

[0300] 28. The method of any one of items 12-27, wherein the optical retardation of the glass-ceramic is less than 15 nm / mm thickness.

[0301] 29. The method according to any one of items 12 to 28, further comprising:

[0302] Maintaining the nucleation temperature for a first predetermined period of time (t N ) to produce a nucleated crystallizable glass composition;

[0303] Among them, (103–0.260T N +0.000203(T N ) 2 –7.96t N +0.1532(t N ) 2 –0.019T C –0.000008(T C ) 2 –10.03t C +0.00597T N *t N +0.00463t N *T C +0.01342T C *t C )<0.2.

[0304] 30. A method for controlling the haze of a glass-ceramic product, the method comprising:

[0305] The nucleation temperature (T N ), the first predetermined time period (t N ), crystallization temperature (T C ) and a second predetermined time period (t C ) is selected so that (103–0.260T N +0.000203(T N ) 2 –7.96t N +0.1532(t N ) 2 –0.019T C –0.000008(T C ) 2 –10.03t C +0.00597T N *t N +0.00463t N *T C +0.01342T C *t C )<0.2.

[0306] 31. The method according to item 30, further comprising:

[0307] The glass composition is heated to a nucleation temperature (T N );

[0308] Maintaining the nucleation temperature for the first predetermined period of time (t N ) to produce a nucleated crystallizable glass composition;

[0309] The nucleated crystallizable glass composition is heated to a crystallization temperature (T C );as well as

[0310] Maintaining the crystallization temperature for the second predetermined period of time (t C ) to produce glass ceramic products.

Claims

1. A glass ceramic product comprising: a first surface; a second surface opposite to the first surface; one or more crystalline phases; a residual glass phase, wherein the residual glass phase is less than or equal to 50 weight percent of the glass-ceramic article; a compressive stress layer extending from the first surface to a depth of compression (DOC); Maximum central tension greater than 70MPa; More than 22J / m 2 The stored tensile energy ZrO2 is in the range of 1.7 mol% to 4.5 mol%, and the ratio of Li2O (mol%) / R2O (mol%) is greater than 0.85, wherein R2O is the sum of alkali metal oxides; And any one or more of the following: (a) a crush toughness greater than 1.0 MPa√m, wherein the crush toughness is measured on a glass-ceramic having a composition and phase assembly equivalent to the composition and phase assembly at the center of the glass-ceramic article; and a haze less than 0.2; (b) a Young's modulus greater than 95 GPa, wherein the Young's modulus is measured on a glass-ceramic having a composition and phase assembly equivalent to the composition and phase assembly at the center of the glass-ceramic article; and a haze less than 0.

2.

2. The glass-ceramic product according to claim 1, wherein: The one or more crystalline phases include petalite.

3. The glass-ceramic product according to claim 1, wherein: The one or more crystalline phases include lithium disilicate.

4. The glass-ceramic product according to claim 1, wherein: The sum of the crystalline phases other than lithium disilicate and petalite is less than 2% by weight of the glass-ceramic article.

5. The glass-ceramic product according to claim 1, wherein: The glass-ceramic article is transparent and has a transmittance of at least 85% for light in the wavelength range of 450 nm to 800 nm for a thickness of 1 mm.

6. The glass-ceramic product according to any one of claims 1 to 5, wherein: When subjected to the fragment test, the glass-ceramic article breaks into less than 5 fragments.

7. The glass-ceramic product according to any one of claims 1 to 5, wherein: The maximum central tension is in the range of greater than 90 MPa to 180 MPa.

8. The glass-ceramic product according to any one of claims 1 to 5, wherein: The stored tensile energy is greater than 22 J / m 2 Up to 60J / m 2 range.

9. The glass-ceramic article of any one of claims 1-5, further comprising grains having a longest dimension of 150 nm or less.

Citation Information

Patent Citations

  • Systems and methods for measuring a profile characteristic of a glass sample

    US8854623B2